#### Answer

$B'(u)=10u^4-16u^3-3u^2+4u-4$

#### Work Step by Step

$B(u)=(u^3+1)(2u^2-4u-1)$
Use the product rule.
$B'(u)=(u^3+1)(4u-4)+(2u^2-4u-1)(3u^2)$
Distribute.
$B'(u)=4u^4-4u^3+4u-4+6u^4-12u^3-3u^2$
Combine like terms.
$B'(u)=10u^4-16u^3-3u^2+4u-4$

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

$B'(u)=10u^4-16u^3-3u^2+4u-4$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.